Serviço social e educação: desvelando o processo de trabalho do assistente social na Unipampa campus São Borja - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This Final Graduate Work is characterized by a Theoretical Practice Report , considering the experience Supervised Training in Social Work I and II , conducted by the Social Service of the Federal University of Pampa ( UNIPAMPA ) , having as main objective to unveil the process of Social work Assistant in San Borja UNIPAMPA campus . For the construction of this work , we performed literature from authors that question the historical process of the Brazilian educational policy research , whereas this work results of internship experience , which was also conducted archival work from the internship documents beyond institutional documents, such as resolutions , laws , management reports on the work makes sense UNIPAMPA.Nesse a ransom of key moments in the history of educational policy . Following concepts of education and social work are discussed . Shortly after thorough discussion is around the Student Assistance and how it is organized today specifically in São Borja campus and ultimately looking to point the working process of the social worker in San Borja UNIPAMPA campus, thus underscoring the professional act beyond the systematization theoretical and practical permeating this socio- occupational space.
Keywords: Ensino superior; Estudantes - Programas de assistência; Serviço Social; Unipampa; Higher education; Students - Assistance programs; CNPQ::CIENCIAS SOCIAIS APLICADAS